Women of the Past, Issues for the Present - Koefoed, Nina Javette; Raja, Rubina (Brepols, 2024)
The roles played by women in history, and even the very idea of what it is to be female, have always been in flux, changing over centuries, between cultures, and in response to diverse social and economic parameters. Even today, women’s roles and women’s rights continue to face changes and pressures. In establishing the series <span class=